If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + 11 = 11 Reorder the terms: 11 + Y = 11 Add '-11' to each side of the equation. 11 + -11 + Y = 11 + -11 Combine like terms: 11 + -11 = 0 0 + Y = 11 + -11 Y = 11 + -11 Combine like terms: 11 + -11 = 0 Y = 0 Solving Y = 0 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = 0
| 11=3n-10 | | -29x+2=-2x+1 | | -7(b+3)=7 | | (x+18)(x-6)=25 | | 3b-1(6-b)=22 | | x+3x=50000 | | 2r=72 | | 2(x+4)=4+4x | | Z^2-2z-24=0 | | 38(24-3.5x)=16(3x-10)+76.5 | | u^2+u-52=0 | | 3(x+2)=-2(x+4) | | -4(e+6)=-12 | | 4x+3=1x | | .65l+70=l | | 12x-5=24x+3 | | -4.65+0.19x=14.92 | | 20x-3+5x=22 | | 7y-5=9y+25 | | 0.12(y-6)+0.18y=0.04y-0.05(30) | | k-12=34 | | 4x^2+39x+56=0 | | -14=7(s-7) | | 15=(3h-1) | | 2-7[9-(6y-6)]= | | -4.65+0.19x=23.85 | | 7.4p-9.2p=-2.6+5.3 | | 5x^2-9x-80=0 | | -4+5x=-4x-4 | | Y-12=24 | | 7=4(5-2x)+3y | | 3(h-4)=-.5(24-6h) |